Synthesis method of 2, 5-furandicarboxylic acid

By oxidizing 5-hydroxymethylfurfural with a heterogeneous catalyst containing ruthenium at high temperature, the problems of easy poisoning and loss of activity of metal catalysts in the prior art are solved, and high-efficiency and low-cost 2,5-furandicarboxylic acid is achieved. Production and recovery of high purity products by simple separation methods.

CN119409671APending Publication Date: 2025-02-11NOVAMONT SPA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411534864.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The metal catalysts used in the existing HMF oxidation methods are prone to poisoning and lose catalytic activity, resulting in high production costs and low yields, and difficult to achieve high selectivity and simple product recovery.

Method used

Using a heterogeneous catalyst containing ruthenium, the pH conditions are controlled in the presence of molecular oxygen and strong base, and oxidation of 5-hydroxymethylfurfural at a temperature above 100°C to form 2,5-furandicarboxylic acid. The method separates the catalyst by simple filtration and reusing it at high temperatures to maintain catalytic activity.

Benefits of technology

A high yield of 2,5-furandicarboxylic acid is achieved, and the catalyst can be recycled multiple times, with a yield of more than 85%, and the product is recovered in high purity through nanofiltration and other methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111309650000051
    Figure BDA0005111309650000051
  • Figure BDA0005111309650000061
    Figure BDA0005111309650000061
  • Figure BDA0005111309650000171
    Figure BDA0005111309650000171
Patent Text Reader

Abstract

The present invention relates to 2, 5-furandicarboxylic acid (FDCA) compositions characterized in that the purity of 2, 5-furandicarboxylic acid is greater than 99%, the inorganic salt content is less than 500 ppm and the residual monocarboxylic acid content is less than 1% by weight compared to the weight of FDCA. FDCA composition for use in a polymerization reaction and obtained by a synthesis process of 2, 5-furandicarboxylic acid (FDCA) comprising the steps of: (1) oxidizing an aqueous solution of 5-hydroxymethylfurfural (HMF) at a temperature above 100 DEG C in the presence of molecular oxygen, a heterogeneous catalyst comprising ruthenium and a strong base to obtain a reaction product in the aqueous solution comprising a salt of an FDCA acid; (2) separating the heterogeneous catalyst from the reaction product in the aqueous solution, and (3) reusing the heterogeneous catalyst in the oxidation reaction in step (1).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application No. 202080093588.3. The project leading to the present invention was funded by the BioBased Industries Joint Undertaking Public-Private Partnership under the European Union's Horizon 2020 research and innovation programme under grant agreement No. 745766.

[0002] The present invention relates to a method for synthesizing 2,5-furandicarboxylic acid (FDCA) by oxidizing 5-hydroxymethylfurfural (HMF).

[0003] 2,5-Furandicarboxylic acid is an oxidized derivative of 5-hydroxymethylfuronic acid, which can be used as a monomer for the production of plastics, especially polyesters. In addition, since HMF is obtained from sugars, it is a derivative obtained from a raw material that is widely available in nature.

[0004] Processes for the oxidation of HMF which give 2,5-furandicarboxylic acid as the main product are known in the literature.

[0005] Document US 4,977,283 (Hoechst) describes a process for the oxidation of HMF in the presence of a metal catalyst belonging to the platinum group, carried out in an aqueous environment with a maximum pH of 8. The patent shows that by controlling the pH, the ratio between the different oxidation products and by-products can be influenced. According to the instructions included in the patent, the pH can be controlled by a base (such as sodium hydroxide or potassium hydroxide), an acid or a buffer solution, the pH being generally kept below 8. The oxidation reaction is carried out at a temperature between 30° C. and the boiling point of water, preferably between 60° C. and 90° C.; the reaction yields compared to the theoretically achievable yields are expressed relative to the disodium salt of 2,5-furandicarboxylic acid in aqueous solution, and the examples do not show the recovery of the product.

[0006] US patent application 2008 / 0103318 (Battel le) describes a process for the oxidation of HMF catalyzed by supported platinum. Here, the selectivity changes with pH, ​​which must be kept at a value of 7 or below, possibly using weak bases such as carbonates and bicarbonates. 2,5-Furandicarboxylic acid is one of the oxidation products described. The use of strong bases such as NaOH is not recommended, as it can lead to side reactions such as disproportionation reactions (Cannizzaro reaction).

[0007] However, the metal catalysts used in the above HMF oxidation processes can become poisoned and thus lose catalytic activity. This means that the catalysts often need to be replaced or regenerated, which increases the cost of the expensive use of precious metals such as platinum.

[0008] Another process for the platinum-catalyzed production of FDCA is described in patent EP 2 601 182 B1, in which reuse of the catalyst is made possible via the presence of a weak base; the examples show the use of NaHCO 3 or basic magnesium carbonate and are carried out at a temperature of 100° C.

[0009] Patent application WO 2016 / 028488 A1 describes a method of oxidation, wherein an aqueous solution containing at least 5% by weight of HMF is contacted with a pH neutral or acidic oxygen source in the presence of a heterogeneous ruthenium-based catalyst. However, the method is limited in its selectivity to FDCA, which reaches a maximum of 60 mol% in the different oxidation products identified. This maximum value is also obtained under a very high oxygen partial pressure (70 bar). In addition, the reaction product is solid, and complex operations are required to separate them from heterogeneous catalysts. Therefore, there is still the problem of selectively obtaining high-yield FDCA and reclaiming the product via a simple separation operation, so that industrial production is efficient, including from an economic point of view.

[0010] There is also a need to produce FDCA having properties that make it suitable for use in polymerization processes. The low selectivity of known processes generally leads to the formation of numerous by-products, such as oligomers and molecules with one functional group, salts or conjugated organic substances that can color the product and affect the polymerization process.

[0011] On the other hand, the method for synthesizing 2,5-furandicarboxylic acid according to the present invention has the significant advantage of providing 2,5-furandicarboxylic acid in high yield using a heterogeneous catalyst containing ruthenium, which can be separated by simple filtration and recycled several times while maintaining its catalytic activity. In addition, FDCA is obtained in a dissociated form in the reaction environment; due to its solubility in water, it can be easily recovered from the catalyst or purified via solid / liquid separation without the need to use an organic solvent.

[0012] According to a first aspect, the present invention therefore relates in particular to a process for the synthesis of 2,5-furandicarboxylic acid by oxidation of an aqueous 5-hydroxymethylfurfural solution catalyzed by a heterogeneous catalyst comprising ruthenium in the presence of molecular oxygen and a strong base under controlled pH conditions at a temperature preferably above 100°C.

[0013] Under such conditions, despite the use of a strong base, a heterogeneous catalyst comprising ruthenium is surprisingly selective for 2,5-furandicarboxylic acid, even in the presence of air as oxidant, and suffers even less from fouling of the catalyst surface than known processes.

[0014] Once separated from the reaction product in dissociated form in aqueous solution, the heterogeneous catalyst can thus be recycled several times in the oxidation reaction while maintaining a high yield of FDCA, even in small amounts compared to the HMF reagent. The aqueous solution containing the reaction product in dissociated form is then subjected to one or more optional purification steps and finally acidified to provide FDCA in solid form.

[0015] Furthermore, the procedure according to the invention makes it easy to obtain 2,5-furandicarboxylic acid particularly suitable for use as a monomer, in particular for the synthesis of polyesters. In fact, a monomer having a low yellowness index (an indicator for the elimination of oligomers capable of interfering with polymerization) is obtained via simple nanofiltration of the dissociated form of the salt of 2,5-furandicarboxylic acid.

[0016] According to another aspect, the present invention therefore relates to a process for purifying FDCA comprising a step of nanofiltration of an aqueous solution of FDCA in dissociated form, preferably in the form of the sodium salt. After this nanofiltration step, the operation of purifying FDCA in solid form is further facilitated by the absence of oligomers, since a simple washing with water is sufficient to obtain a FDCA composition with high purity, in particular with a limited content of impurities with a single functional group, making it particularly suitable for use as a monomer for polyester synthesis.

[0017] According to another aspect, the present invention therefore relates to an FDCA composition having a high purity and a low content of inorganic salts and residual monocarboxylic acids.

[0018] The present invention will be described in more detail below.

[0019] A first object of the present invention is a method for synthesizing 2,5-furandicarboxylic acid (FDCA), said method comprising the following steps:

[0020] 1) oxidizing an aqueous solution of 5-hydroxymethylfurfural (HMF) at a temperature above 100° C. in the presence of molecular oxygen, a heterogeneous catalyst comprising ruthenium and a strong base to obtain a reaction product comprising a salt of FDCA acid in aqueous solution;

[0021] 2) separating the heterogeneous catalyst from the reaction product in aqueous solution,

[0022] 3) Reusing the heterogeneous catalyst in the oxidation reaction in step 1).

[0023] The present invention also relates to the following embodiments:

[0024] 1. The synthesis method of 2,5-furandicarboxylic acid (FDCA) comprises the following steps:

[0025] 1) oxidizing an aqueous solution of 5-hydroxymethylfurfural (HMF) at a temperature above 100° C. in the presence of molecular oxygen, a heterogeneous catalyst comprising ruthenium and a strong base to obtain a reaction product in aqueous solution comprising a salt of FDCA acid;

[0026] 2) separating the heterogeneous catalyst from the reaction product in aqueous solution,

[0027] 3) Reusing the heterogeneous catalyst in the oxidation reaction in step 1).

[0028] 2. The method according to claim 1, wherein the strong base has a solubility of 45 g / l or more in water at 25°C.

[0029] 3. The process according to any one of claims 1 to 2, wherein the pH is maintained at 6.5 to 9 during the oxidation in step 1).

[0030] 4. The process according to any one of claims 1 to 3, wherein the oxidation in step 1) is carried out at a temperature below 160°C.

[0031] 5. according to the method for any one of claims 1 to 4, wherein the heterogeneous catalyst comprising ruthenium is selected from supported ruthenium, supported ruthenium oxide, unsupported ruthenium oxide, supported ruthenium hydroxide, unsupported ruthenium hydroxide and mixtures thereof.

[0032] 6. The process according to any one of claims 1 to 5, wherein the separation of the heterogeneous catalyst in step 2) is carried out by at least one operation selected from the group consisting of filtration, decantation, centrifugation and separation by an electrochemical cell, an electrostatic precipitator, a wet scrubber or a hydrocyclone.

[0033] 7. The process according to claim 6, wherein the separation of the heterogeneous catalyst in step 2) is carried out via at least one tangential flow microfiltration.

[0034] 8. The process according to any one of claims 1 to 7, wherein the catalyst is washed and / or regenerated after step 2) and before reuse in step 3).

[0035] 9. The process according to any one of claims 1 to 8, wherein after step 2), the reaction product in aqueous solution is purified by at least one nanofiltration operation.

[0036] 10. The process according to claims 8 and 9, wherein the catalyst is washed with water and the resulting catalyst washing water is used in a purification operation by nanofiltration.

[0037] 11. The process according to claim 1, wherein the reaction product in aqueous solution is subjected to neutralization and the FDCA acid obtained in solid form is subsequently isolated.

[0038] 12. FDCA composition characterized in that the purity of 2,5-furandicarboxylic acid is greater than 99%, the content of inorganic salts is less than 500 ppm and the content of residual monocarboxylic acid is less than 1% by weight, based on the weight of FDCA.

[0039] 13. Use of a composition according to claim 12 in a polymerization reaction.

[0040] 14. A method for purifying FDCA, comprising a step of nanofiltration of an aqueous solution of FDCA in dissociated form, followed by a step of precipitating FDCA and a step of washing the obtained solid form of FDCA with water.

[0041] The reaction product in the aqueous solution containing the salt of the FDCA acid separated in step 2) above is advantageously neutralized, after possibly undergoing one or more optional purification operations, to allow the FDCA acid obtained to be subsequently isolated in solid form. This method advantageously involves the use of a catalytically active phase in an amount ranging from 0.5% to 10% by weight relative to the weight of HMF. It also offers the possibility of recycling the catalyst several times while maintaining a reaction yield greater than 85%, advantageously greater than 90%.

[0042] The starting material which is subjected to oxidation in step 1) of the process according to the invention is an aqueous solution of 5-hydroxymethylfurfural (HMF).

[0043] HMF can be obtained by dehydration of sugars, in particular from hexose, such as fructose and glucose derived from the hydrolysis and possible isomerization of biomass containing polysaccharides. The dehydration reaction can be carried out according to a variety of techniques, which generally involve the use of acid catalysts and may or may not involve the use of aqueous and non-aqueous solvents. For example, HMF obtained by methods using quaternary ammonium salts such as those described in patents EP 2 994 458B1, EP 3 207 032B1 or PCT / EP2019 / 068860 is a suitable starting material.

[0044] The HMF used as starting material for the process according to the invention may contain by-products of sugar processing.

[0045] It is advantageous to use an aqueous solution of HMF with a high purity. For example, an aqueous solution prepared from an HMF composition having a purity of preferably more than 98.5% and a quaternary ammonium salt content converted to nitrogen atoms of less than 0.25% by weight, preferably less than 0.1% by weight, compared to HMF, is particularly suitable. The presence of an excess of quaternary ammonium salts may actually adversely affect the selectivity of the catalyst due to interaction with the active phase.

[0046] The purity of HMF is determined, for example, by HPLC / UV analysis with external calibration. For example, HPLC / UV analysis can be performed using, for example, a "Phenomenex Gemini NX-C18" column (150 mm×3.0 mm×5 μm; flow rate: 0.5 mL / min; column temperature: 30° C.) and (A) 1% v / v aqueous HCOOH solution and (B) acetonitrile as eluents, with the following gradient:

[0047]

[0048]

[0049] The nitrogen content is determined, for example, by elemental analysis or ion chromatography using a conductivity detector (CI-CD). The amount of nitrogen from the quaternary ammonium salt can be determined stoichiometrically, for example, by using an external standard to quantify the ammonium cation by CI-CD chromatography using a Metrosep C4-100 column (100 mm×4.0 mm×5 μm, flow rate: 1.0 mL / min, column temperature: 30° C.) and a mixture of aqueous nitric acid (7.5 mmol / L) and 20% v / v acetonitrile as eluent.

[0050] HMF compositions having one or more components selected from organic acids, compounds having at least one ketone or aldehyde functional group (other than HMF), dimers, oligomers and humins formed as by-products of the dehydration reaction of the starting sugars are preferred, the total amount of which is less than 4 wt.%, preferably less than 3 wt.%, more preferably less than 1 wt.%, relative to the weight of HMF. HMF compositions having a furfural content of less than 0.10 wt.%, relative to the weight of HMF, are also particularly preferred.

[0051] Advantageously, the initial HMF composition comprises fructose and / or sugar anomers in an amount of less than 3 wt.-%, preferably less than 0.5 wt.-% and even more preferably less than 0.1 wt.-% compared to the weight of HMF. The fructose content can be determined, for example, by IC-PAD analysis using a column such as Metrosep Carb 2 (250 mm×4.0 mm×5 μm, flow rate: 0.7 mL / min, column temperature: 30° C.) and isocratic elution with aqueous NaOH solution.

[0052] An example of a suitable composition is a composition obtained by the method described in patent application PCT / EP2019 / 068860.

[0053] In the process according to the invention, the oxidation of HMF takes place in aqueous solution and does not require the use of organic solvents, since the pH conditions ensure that the product of the oxidation reaction, which is present in dissociated form, is readily soluble in water as well as in HMF. The initial concentration of HMF in the aqueous solution is advantageously between 1.5% and 35% by weight, preferably between 2% by weight (corresponding to a HMF:H2O weight ratio of 1:50) and 20% by weight, more preferably between 2% and 10% by weight.

[0054] In the process according to the invention, the oxidizing substance responsible for the oxidation of HMF is molecular oxygen or a compound containing molecular oxygen, such as air, oxygen-enriched air or a mixture of oxygen and an inert gas. The reaction is advantageously carried out in a closed reactor under pressure or by passing O2, air or air enriched with O2 into the reactor.

[0055] Although high oxygen pressures are advantageous, the method according to the invention has the particular advantage that they are not necessarily required. In fact, the method according to the invention is advantageously carried out even in air at a pressure higher than atmospheric pressure but not greater than 2 MPa (20 bar), and therefore at an oxygen partial pressure less than or equal to 0.5 MPa (5 bar). This makes it possible to limit the amount of CO2 produced during the synthesis via the influence of combustion phenomena at high temperatures.

[0056] The oxidation step in the process according to the invention is carried out in the presence of a heterogeneous catalyst containing ruthenium. This catalyst is advantageously selected from: supported ruthenium metal, supported ruthenium oxide, unsupported ruthenium oxide, supported ruthenium hydroxide, unsupported ruthenium hydroxide and mixtures thereof; particularly preferably, supported ruthenium metal or a mixture of supported ruthenium oxide and hydroxide is used, preferably in the form of RuO2 and Ru(OH) x in the form of , wherein x is advantageously between 2 and 4, preferably equal to 2 or 4, more preferably equal to 4. The ruthenium oxide in the process catalyst according to the invention may be in hydrated form.

[0057] The most suitable materials for forming the support of the catalyst are, for example, carbon, non-metallic oxides (such as silicon dioxide and graphene oxide), functionalized graphite and combinations thereof, optionally in the form of multiple layers, carbon being particularly preferred. The support material may be in nanostructured and / or functionalized form; it contains the catalytically active phase in an amount of preferably 0.5% to 20% by weight, more preferably 1% to 10% by weight, compared to the catalyst, so that the stationary phase has a good dispersion on the support surface.

[0058] In the present invention, the preferred catalyst, more specifically the catalytic support, is a microporous structure having a high specific surface area (i.e., a width of not more than about 2.0 nm according to IUPAC classification). The pores of the catalyst are preferably pores of 600-1200 m2, which advantageously facilitates high dispersion of the active catalytic phase to improve overall activity and selectivity. Ultramicroporous structures (pore diameter of 7-20 angstroms) and ultramicroporous structures (pore diameter of less than 7 angstroms) are particularly preferred. The specific surface area of ​​the catalyst according to the present invention is preferably 600-1200 m2. 2 / g, more preferably 700-1100m 2 / g, even more preferably 800-1000m 2 / g.

[0059] Therefore, the supported catalyst according to the present invention preferably has a molecular weight of 800 to 1600 m 2 The preparation of a support with a specific surface area of ​​1.1747 W / g was started.

[0060] The specific surface area can be measured according to the BET method disclosed in S. Brunauer, PH Emmett and E. Teller, J. Am. Chem. Soc. 1938, 60, 309, in which the amount of gas adsorbed on the surface of a material is measured.

[0061] Depending on the value of the specific surface area of ​​the material, nitrogen or helium is used as gas.

[0062] The BET surface area of ​​mesoporous materials (values ​​of 50-400 m 2 / g) is measured here as follows: at about 0.13×10 -3 After the catalyst sample was degassed overnight at 100 °C in a vacuum of 1.5 Pa, the amount of nitrogen adsorbed at 77 K and a P / Po of about 0.3 was determined and assumed to be The cross-sectional area of ​​nitrogen or argon gas.

[0063] The BET specific surface area of ​​microporous materials (values ​​are 400-1000m 2 / g) is measured here as follows: at about 0.13×10 -3After the catalyst sample was degassed overnight at 100 °C in a vacuum of 1.5 Pa, the amount of helium adsorbed at 4.2 K and a P / Po of about 0.3 was determined and assumed to be The cross-sectional area of ​​helium.

[0064] According to a preferred aspect of the present invention, the cumulative pore volume of the catalyst is preferably in the range of 0.25 to 0.8 cm 3 / g, preferably 0.3 to 0.6 cm 3 / g, and its micropore specific surface area is preferably 900 to 1100m 2 / g, and the micropore size is preferably 3.5 to 5 angstroms.

[0065] The catalyst based on ruthenium in supported form, whether it is ruthenium metal, oxide or hydroxide or mixtures thereof, can be prepared according to techniques known to those skilled in the art.

[0066] For example, supported oxides and hydroxides can be prepared by finely dispersing the metal salt on the substrate via grafting, sol-gel, thermal treatment, steam explosion, combustion, deposition, adsorption from solution, coprecipitation or impregnation (eg by incipient wetness impregnation or CVD (chemical vapor deposition)).

[0067] The step of preparing the catalyst may be carried out separately from the oxidation process according to the present invention, or may be carried out in a preliminary step of the oxidation process according to the present invention.

[0068] According to one aspect of the present invention, the catalyst contains ruthenium as the active catalytic substance, which may be combined with a structural promoter capable of improving its performance. For example, oxides and mixed oxides of metals may act as structural promoters.

[0069] The process according to the invention can optionally be carried out in the presence of one or more catalysts other than ruthenium, selected from, for example, platinum, palladium, iron, manganese, copper, cobalt, nickel. These metals can be used in the form of supported catalysts and in the form of mixed metals (for example polyoxometalates).

[0070] In a preferred embodiment of the process according to the invention, the catalyst comprises, or more preferably consists of, carbon-supported Ru, preferably in an amount of 1 to 10 wt.-%, preferably in combination with a structural promoter such as sodium, cesium, barium, potassium, bismuth (e.g. Na2O).

[0071] According to one aspect of the present invention, during the oxidation reaction, a mixed ruthenium oxide and hydroxide such as Ru(OH) is formed in situ from ruthenium metal in the presence of a dilute strong base such as NaOH. x +RuO2 / C.

[0072] In another preferred embodiment of the process according to the invention, the catalyst comprises Ru(OH) supported on carbon. x , or more preferably consisting thereof.

[0073] In another preferred embodiment of the process according to the invention, the catalyst comprises ruthenium oxide, or more preferably consists of ruthenium oxide, preferably in combination with a structural promoter such as sodium, cesium, barium, potassium, bismuth (eg Na2O).

[0074] The catalyst used in the process according to the invention is used in limited amounts compared to the amounts of reagents. Advantageously, the amount of metal catalyst is less than 10% by weight relative to the weight of HMF, preferably less than 8% by weight relative to the weight of HMF, even more preferably less than 6% by weight relative to the weight of HMF; the catalyst is advantageously present in an amount greater than 0.5% by weight, preferably greater than 0.6% by weight, even more preferably greater than 0.7% by weight relative to the weight of HMF.

[0075] The oxidation reaction of 5-hydroxymethylfurfural is carried out at a temperature higher than 100°C, but preferably lower than 160°C, more preferably 150°C or lower, advantageously 140°C or lower.

[0076] In the presence of a ruthenium-based catalyst, the catalytic efficiency is higher for oxidation temperatures of 110°C or higher, so a temperature of 120°C or higher is preferred, and a temperature of 130°C or higher is more preferred.

[0077] The strong base required for carrying out step 1) of the present invention preferably has a solubility in water of 45 g / l or more at 25°C, more preferably 100 g / l or more, even more preferably 200 g / l or more. Advantageously, the strong base of the present invention is selected from sodium hydroxide, potassium hydroxide, ammonia, ammonium hydroxide, barium hydroxide, lithium hydroxide, cesium hydroxide, strontium hydroxide, rubidium hydroxide, trimethylamine, methylamine, diethylamine. Soluble bases having a hydroxyl group are preferred, and sodium hydroxide is particularly preferred, because it facilitates the subsequent purification operation.

[0078] These bases have the function of bringing the initial reaction mixture to a neutral pH and then buffering the acidity resulting from the formation of FDCA; they are used in the amount necessary to maintain the pH of the reaction environment between 6.5 and 9.

[0079] These strong bases are preferably added gradually during the reaction as a function of the reaction rate (and therefore the pH change), avoiding as much as possible the presence of excess base in the reaction mixture, which could lead to condensation reactions and the formation of sodium oxide, which has a passivating effect on the active phase of the catalyst.

[0080] Therefore, the pH is favorably 7 or higher and 8.5 or lower, preferably greater than or equal to 7.5 and less than or equal to 8.

[0081] Under these conditions, it has been determined that the catalyst retains its catalytic activity almost unchanged and its reuse allows the selective production of FDCA with almost complete conversion of HMF. It can be recycled several times while continuing to maintain an FDCA yield of more than 90%.

[0082] If the reaction is carried out by introducing a poorly soluble base such as basic magnesium carbonate instead of sodium hydroxide, it tends to settle on the surface of the catalyst, reducing its activity compared to the use of gradually fed NaOH, thus limiting the possibility of its recycling.

[0083] The strong base is preferably fed as a conveniently diluted aqueous solution, ie in a concentration of preferably 50 g / kg to 350 g / kg, more preferably 150 g / kg to 300 g / kg.

[0084] This oxidation step 1) is preferably carried out in a reactor which is suitably stirred or in any case capable of ensuring a high gas-liquid-solid interface area, for example a reactor with internal or external recirculation, a reactor with mechanical stirring or gas-induced stirring, or a fixed bed, for example a jet loop or air-lift type reactor. In addition to limiting the reaction time, which is generally in the range of 12 hours to 6-8 hours, this feature also has a positive influence on the catalyst activity and selectivity.

[0085] At the end of the oxidation reaction (step 1), the 2,5-furandicarboxylic acid produced according to the invention is present in dissociated form in the aqueous solution.

[0086] In step 2) of the process according to the invention, the heterogeneous catalyst is separated from this reaction product in aqueous solution using known techniques.

[0087] According to one aspect of the process of the present invention, the heterogeneous catalyst in step 2) is separated by at least one operation selected from the group consisting of filtration, decantation, centrifugation and separation by an electrochemical cell or electrostatic precipitator, wet scrubber or hydrocyclone.

[0088] This separation is advantageously carried out via one or more identical or different filtration operations carried out in series or in parallel, for example belt filtration, drum filtration, filter press filtration, candle filtration.

[0089] Among the filtration operations, microfiltration and ultrafiltration are preferred, via membranes of suitable materials and performed, for example, with tangential flow.

[0090] Tangential flow microfiltration (TFF), preferably performed on sintered steel or ceramic membranes, is particularly suitable for catalyst separations.

[0091] According to a preferred aspect of the process of the invention, in step 2) the heterogeneous catalyst is separated from the reaction products via at least one tangential flow microfiltration, which microfiltration is advantageously accompanied by one or more washings of the catalyst with water.

[0092] This filtration operation is advantageously carried out at an alkaline pH and a temperature above 40° C. in order to keep the FDCA salt in solution.

[0093] According to step 3) of the process according to the invention, the catalyst thus separated off in step 2) can be reused in the oxidation step 1) as such or preferably after washing and / or regeneration.

[0094] According to this step 3), the catalyst separated in step 2) can be fed alone or preferably together with an aliquot of fresh catalyst to the oxidation reaction in step 1). This feed is advantageously in the form of an aqueous slurry with a concentration preferably not exceeding 95% by weight, so that keeping the catalyst in suspension actually helps to maintain the correct catalytic activity.

[0095] These operations of washing and / or regeneration of the separate catalyst in step 2) are advantageously carried out using water and at a temperature ranging from 40 to 60° C. in order to dissolve any reaction products and by-products that may be adsorbed on the catalyst surface and to limit fouling of the active phase.

[0096] The amount of water used varies according to the amount and nature of the reaction products and by-products present; several repetitions of the washing operation are advantageously carried out.

[0097] According to a preferred aspect, the catalyst washing water is reused for diluting the reaction product during the subsequent operation of purifying the 2,5-furandicarboxylate. This mode of operation is particularly advantageous because it enables the use of small amounts of water overall while increasing the recovery yield.

[0098] Once the catalyst has been separated, FDCA in solid form can be obtained by neutralizing the reaction product in an aqueous solution. The FDCA thus obtained is easily recovered using known techniques, such as one or more separation operations selected from filtration, decantation, centrifugation. Alternatively, FDCA in solid form can be obtained by crystallization from an aqueous solution of FDCA in salt form and subsequent filtration.

[0099] Neutralization of the reaction product is advantageously achieved by adding a mineral acid such as sulfuric acid, hydrochloric acid, nitric acid or acetic acid in a concentration of preferably 20% to 70%, more preferably 40% to 60%.

[0100] If the strong base used in the first step is caustic soda, sulfuric acid is advantageously used.

[0101] A person skilled in the art will be able to easily determine a precipitation method (e.g., in terms of the amount and method of adding acid) that will enable the optimum particle size of the precipitate and its recovery level to be obtained, thereby limiting the incorporation of inorganic salts formed in the precipitate itself and other organic byproducts or intermediates that may be present. The particle size of the precipitate affects the recovery and final purification of the FDCA produced in solid form. The solid form of FDCA is purified according to known techniques. It can be carried out, for example, by washing and subsequent solid / liquid separation before final drying, by a crystallization operation or by extraction with an organic solvent (e.g., acetone, methanol, ethanol).

[0102] In the solid / liquid separation, filtration operations are preferred; suitable examples of these are candle filtration, belt filtration, rotary filtration (drum centrifuge), filter pressing, while candle filtration and belt filtration are preferred. These operations are preferably carried out when hot (50-60° C.), but have the advantage that they do not require reaching high temperatures that favor condensation phenomena; they can be promoted by diluting the reaction product with water. They also make it possible to remove salts originating from the acidification operation and partial oxidation products of HMF (such as residual monocarboxylic acids), which affect the properties of the final product. They also allow further washing of FDCA in solid form.

[0103] According to a particularly advantageous aspect, when the FDCA is separated off in solid form by filtration, the neutralized reaction product is appropriately diluted by using catalyst wash water.

[0104] According to a particularly preferred embodiment of the invention, after step 2) and before FDCA precipitation, the process comprises an (optional) step of purifying the salt of 2,5-furandicarboxylic acid present in the reaction product using known techniques, for example via one or more membrane separation operations (filtration), by bleaching ion exchange resins or hydrogenation. This purification is preferably carried out via at least one nanofiltration membrane filtration operation; this operation effectively removes high molecular weight condensation products (oligomers) that would color the final product from the 2,5-furandicarboxylic acid salt.

[0105] The colorimetric analysis of the solid FDCA obtained by spectrophotometry according to the described embodiment in fact shows a yellowness index (yellowness index, YI) advantageously lower than 20, more advantageously lower than 15 and even more advantageously equal to or lower than 5. Without wishing to be bound by any theory, the presence of impurities that give rise to such a yellowness index appears to have a negative effect on the polymerization, in particular on the degree of polymerization and on the viscosity (branching).

[0106] Depending on the characteristics of the reaction product to be filtered, a person skilled in the art will be able to select the type of membrane to be used, taking into account the material from which it is made, its electrochemical properties and its porosity. Based on the characteristics of the selected material, a person skilled in the art will also be able to easily select the optimal pH conditions and operating pressure for each separation operation and assess the need for performing one or more diafiltration steps (i.e., diluting the retentate by adding water and repeating the separation operation).

[0107] For example, filtration operations are often performed using organic membranes of natural origin (eg, rubber, polysaccharides) or synthetic membranes (eg, polymer membranes) and inorganic membranes (eg, ceramic, metal, or glass membranes).

[0108] Among the organic membranes, polyamides, polyimides, polyolefins, polyetherimides, polyetherethers, poly(etherketones), polycarbonates, cellulose acetates and derivatives are preferred, and membranes made of polypiperazineamides having low organic salt rejection are particularly preferred.

[0109] Specific examples of suitable organic membranes are polysulfone, aromatic polyamide, polypiperazineamide, polyethylene, polytetrafluoroethylene (PTFE), polypropylene, polyvinyl alcohol, polystyrene, polybenzimidazole (PBI), polyphenylene, polyphosphazene, polyvinylidene fluoride (PVDF), polyethersulfone (PES), polyacrylonitrile (PAN), polyvinyl chloride (PVC).

[0110] Both isotropic (or symmetric) and anisotropic (or asymmetric) membranes and composite membranes are suitable. Anisotropic membranes are preferably used.

[0111] In this method, dense membranes (pore size <1 nm) are preferably used in the optional purification stage. Porous membranes (i.e. having a pore size of 1 nm to 10 μm, such as macroporous membranes of >50 nm, mesoporous membranes of 2 nm to 50 nm or microporous membranes of 1 nm to 2 nm) may also be advantageously used, particularly during step 2) of separating the catalyst from the reaction product.

[0112] The membrane used in the nanofiltration purification step according to the invention has an average pore size of 5 nm or less, even more advantageously corresponding to an average pore size of an amolecular weight cut-off or MWCO of about 700 Da to about 300 Da. These characteristics make the separation of the sodium salt of FDCA particularly efficient.

[0113] The membranes can be formed in different configurations, for example in flat, tubular, capillary or hollow fiber form. Flat membranes can be used as they are in filter press type systems, in rotary systems or wound in spiral modules to increase the surface area / occupied volume ratio.

[0114] The membrane separation operation according to the present invention can be carried out batchwise or continuously; depending on the situation, it is preferred to use normal (vertical) or tangential flow filtration. The membrane separation operation under tangential flow conditions is preferred.

[0115] The nanofiltration operation is preferably carried out according to the invention using a membrane of a material selected from the group consisting of polysulfones, polypiperazineamides, polyamides, polyimides.

[0116] According to a preferred aspect, nanofiltration is performed along tangential flow (TFF) with a spiral wound polymer membrane.

[0117] Several nanofiltration operations are advantageously carried out in series, possibly preceded and / or followed by a series of diafiltrations.The amount of water added varies depending on the amount and type of reaction products and by-products present.

[0118] According to one particularly advantageous aspect, the catalyst wash water is used in a nanofiltration purification operation.

[0119] Those skilled in the art will be able to readily determine appropriate operating conditions for maintaining the sodium salt of FDCA in solution, thereby avoiding excessive dilution, and at the same time minimizing fouling of the membrane.

[0120] For this reason, the concentration of the reaction product subjected to nanofiltration is also preferably kept below 50 g / kg, in order to limit the precipitation of 2,5-FDCA salts, which would tend to cause fouling of the membrane.

[0121] According to this embodiment of the invention, the permeate is advantageously concentrated to a suitable value to facilitate the recovery of FDCA in solution using known techniques, such as by evaporation.

[0122] This concentration is preferably performed by osmosis, taking care to maintain solubility conditions of the FDCA salt to avoid its precipitation on the membrane.

[0123] FDCA was then obtained in solid form as described above.

[0124] Advantageously, the FDCA obtained has a purity of more than 98.5%, more advantageously more than 99% and even more advantageously more than 99.5%, as well as an inorganic salt (e.g. sulfate) content of less than 500 ppm and a residual monocarboxylic acid content of less than 1%, preferably less than 0.5% by weight, relative to the weight of FDCA, making it particularly suitable for use as a monomer in polyester synthesis.

[0125] Therefore, a second object of the present invention is an FDCA composition characterized in that the purity of 2,5-furandicarboxylic acid is higher than 99%, preferably higher than 99.5%, the content of inorganic salts is less than 500 ppm, and the content of monocarboxylic acids is less than 1%, preferably less than 0.5% by weight, more preferably less than 0.1% by weight, relative to the weight of FDCA. Among the monocarboxylic acids, the FDCA composition of the invention advantageously comprises 2-furanacetic acid in an amount of 0.1% by weight or less (preferably 0.05% or less) relative to the weight of FDCA and / or levulinic acid in an amount of 0.1% by weight or less (preferably 0.05% or less) relative to the weight of FDCA.

[0126] Purity and monocarboxylic acid content are determined, for example, by HPLC / PDA analysis after external calibration. For example, HPLC / PDA analysis can be performed using a Rezex column of the type "ROA-Organic Acid H+ (8%)" 300×7.8 mm by isocratic elution of a 0.005 N H2SO4 aqueous solution at a flow rate of 0.6 mL / min at a temperature of 60-65° C., recording at 254 nm and 285 nm.

[0127] The content of inorganic salts, in particular inorganic anions, is determined, for example, by ion chromatography with a conductivity detector (CI-CD), using a "Metrosep A Supp5" 250 mm×4.0 mm×5 μm column on a stationary phase, for example based on polyvinyl alcohol with quaternary ammonium groups, by isocratic elution with an aqueous solution of 3.2 mM Na2CO3+1 mM NaHCO3; flow rate: 0.7 mL / min; column temperature 30°C.

[0128] The invention also relates to the use of such a composition in a polymerization reaction, in particular for the synthesis of polyesters.

[0129] The abovementioned composition can advantageously be obtained by subjecting an aqueous solution of FDCA in dissociated form to at least one nanofiltration step, followed by neutralization, precipitation and purification, with at least one washing with water, followed by solid / liquid separation.

[0130] Therefore, a third object of the present invention is a method for purifying FDCA, which comprises the steps of nanofiltration of an aqueous solution of FDCA in dissociated form, followed by precipitation of FDCA and washing the obtained solid form of FDCA with water.

[0131] According to one aspect of the purification process, the aqueous solution of FDCA in dissociated form is advantageously prepared according to the process described above for the synthesis of 2,5-furandicarboxylic acid, in particular obtained after step 2) of separation from the catalyst.

[0132] According to another aspect, the aqueous solution of FDCA in dissociated form is advantageously prepared by a process comprising the following steps: oxidation of an aqueous solution of HMF in the presence of a gas containing oxygen and a supported catalyst containing a metal of the platinum group, preferably platinum, the step being carried out in an aqueous solution at a pH maintained above 7 and below 12, preferably via the addition of a weak base or gradually adding a strong base. Examples of weak bases are sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, dihydrogen phosphate and triphosphate buffers and mixtures thereof. Even more advantageously, the aqueous solution of FDCA in dissociated form is prepared according to the process for the synthesis of 2,5-furandicarboxylic acid described in patent EP 2 601 182 B1.

[0133] In both cases, the initial HMF solution is advantageously prepared from an HMF composition obtained as described in patent application PCT / EP2019 / 068860.

[0134] The process according to the invention can be carried out both batchwise and continuously and advantageously does not require the use of organic solvents.

[0135] The process according to the invention will now be described in a non-exhaustive manner in the following examples. Example

[0136] The catalyst used in the following examples is composed of an aqueous solution of RuCl3 (8.3 mM) and a catalyst having a specific surface area of ​​1500 m 2 / g of activated carbon support. About 286 mL of solution was used for about 10 g of support. After vigorous stirring for 15 minutes, the solid was separated, washed with demineralized water and dried at 50°C overnight.

[0137] The obtained powder was treated with NaOH (1.0 M, about 28 mL) under stirring for 24 hours. The solid was then dried at 140° C. for another 24 hours to obtain a Ru(OH) 3 / C catalyst containing about 5% ruthenium.

[0138] Example 1

[0139] Step 1)

[0140] 1 kg of 2% HMF aqueous solution (HMF 20 g / kg) and a supported catalyst based on ruthenium hydroxide (Ru(OH) prepared as described above) were mixed. x / C 5%, x=3) were charged into a 2 L autoclave so that the weight ratio of Ru / HMF was 5%.

[0141] The reactor was brought to a pressure of 20 bar with air and heated to an internal temperature of 130°C.

[0142] The reactor was fed with an air flow of 150 NL / h for 16 hours and an aqueous caustic soda solution (150 g / kg) was continuously fed to maintain a constant pH value between 7.5 and 8.

[0143] Step 2)

[0144] The final aqueous solution containing the reaction products (FDCA salt and reaction intermediates) was filtered from the catalyst (through a 0.22 μm diameter Millipore membrane) and analyzed by liquid chromatography-PDA in a Rezex column with 0.005 N H2SO4 eluent (flow rate = 0.6 mL / min; temperature = 60°C).

[0145] A synthesis yield of 88% was obtained, calculated as the ratio of the molar concentration of the salt of 2,5-FDCA in the synthesis solution obtained by chromatographic analysis to the molar concentration calculated theoretically taking into account the initial molar concentration of the HMF solution fed to the process.

[0146] Step 3)

[0147] The catalyst recovered by filtration in step 2) was reused as is under the process conditions reported in step 1). Although the conditions for recovering the catalyst from step 2) were not optimized, a 2,5-FDCA synthesis yield of 78% was obtained, calculated as shown above.

[0148] Comparative Example 1

[0149] Step 1)

[0150] 1 kg of 2% HMF aqueous solution (HMF 20 g / kg) and a supported catalyst based on ruthenium hydroxide (Ru(OH)3 / C 5% as in Example 1) were charged into a 2L autoclave so that the weight ratio of Ru / HMF was 5%. Magnesium hydroxide was added to the reactor at a molar ratio of 1:2 relative to HMF.

[0151] The reactor was brought to a pressure of 20 bar with air and heated to an internal temperature of 130° C. and then fed with an air flow of 150 NL / h for 16 hours.

[0152] Step 2)

[0153] The final aqueous solution containing the reaction products (FDCA salt and reaction intermediates) was separated from the catalyst by filtration (through a 0.22 μm diameter Millipore membrane) and analyzed by liquid chromatography-PDA in a Rezex column with 0.005 N H2SO4 eluent (flow rate = 0.6 mL / min; temperature = 60°C).

[0154] A synthesis yield of 83% was obtained, calculated as the ratio of the molar concentration of the salt of 2,5-FDCA in the synthesis solution obtained by chromatographic analysis to the molar concentration calculated theoretically taking into account the initial molar concentration of the HMF solution fed to the process.

[0155] The isolated catalyst was characterized in terms of specific surface area, pore size distribution and cumulative volume pores and compared with those of the fresh catalyst and the catalyst recovered after Example 1 (catalyst recovered by filtration before its reuse).

[0156]

[0157] A sharp decrease in specific surface area and accessible pore volume can be observed in Comparative Example 1, where an insoluble weak base such as Mg(OH)2 was used. In Example 1, the catalytic properties were instead retained in the presence of a soluble strong base.

[0158] The scaling of the active surface was also confirmed by X-ray Photoelectron Spectroscopy (XPS) analysis of the atomic composition distribution (see table below), which demonstrated the relevant amount of magnesium deposited on the ruthenium relative to sodium, which limits the catalytic activity of the ruthenium oxide / hydroxide:

[0159] catalyst Alkali Ru[%] magnesium[%] sodium[%] Fresh - 1.1 - 1.3 Comparative Example 1 (after first use) <![CDATA[Mg(OH)2]]> 0.1 15.1 1.2 Example 1 (after first use) NaOH 1.05 - 1.8

[0160] XPS spectra were collected using an Escalab 200-C VG spectrometer with a 5-channel accelerator hemispherical analyzer equipped with a dual anode source that transmits non-monochromatic X-radiation corresponding to the Mg Kα line (energy = 1253.6 eV, line width = 0.7 eV) and the Al Kα line (energy = 1486.6 eV, line width = 0.8 eV), respectively, and the pressure in the analysis chamber during the measurement was about 5 × 10 -9 mbar. The analysis area is 3mm 2 .

[0161] Step 3)

[0162] The catalyst recovered by filtration in step 2) was reused as is under the process conditions reported in step 1). A synthesis yield of 2,5-FDCA of only 67% was obtained, calculated as indicated above.

[0163] Example 2

[0164] Step 1)

[0165] 10 kg of 10% HMF aqueous solution (HMF 100 g / kg) and a supported ruthenium hydroxide-based catalyst (Ru(OH) x+RuO2 / C 5%) (wherein x=3) was charged into a 10 L jet loop reactor so that the weight ratio of Ru / HMF was 0.75%.

[0166] The reactor was brought to a pressure of 20 bar with air and heated to an internal process temperature of 130°C.

[0167] The reactor was fed with an air flow of 20 NL / min for 8 hours and an aqueous caustic soda solution (250 g / kg) was continuously fed at a variable flow rate, which was directly managed by the pH management and control equipment for the process steps to maintain the pH value between 7.5 and 8.

[0168] Step 2)

[0169] The final aqueous solution containing the reaction products (FDCA salt and reaction intermediates) was separated from the catalyst by tangential filtration on a 2 μm sintered steel filter and analyzed by liquid chromatography as shown in the above examples.

[0170] Compared to the theoretically calculated synthesis yield of 2,5-FDCA taking into account the initial concentration of the HMF solution fed to the process, a synthesis yield of 2,5-FDCA of 95% was obtained.

[0171] Step 3)

[0172] The catalyst recovered via filtration during step 2) was washed with water at 50°C, filtered and reused under the process conditions reported in step 1). The reuse operation was repeated several times. The table shows the results of the yield, calculated as the ratio of the concentration of 2,5-FDCA salt in the synthesis solution to the concentration theoretically calculated taking into account the initial concentration of the HMF solution fed to the process:

[0173] Reuse Yield (%) I 98.2 II 90.8 III 91.9 IV 90.8

[0174] The 2,5-FDCA salt solution was appropriately diluted to a concentration of 10 g / kg. The solution was treated by a spiral wound membrane nanofiltration system with tangential flow using a membrane with a cutoff value of 300-500 Da in polypiperazineamide. The process described in this manner was carried out at 10-15 L / h / m 2 Operating under constant flow conditions, it was possible to achieve a salt rejection of 38% of the salt from the monomer.

[0175] The retentate contained impurities originating from the aldol condensation phenomenon (coloring matter YI=80).

[0176] The permeate containing the aqueous solution of 2,5-FDCA sodium salt was subsequently concentrated by an osmotic process to a concentration of no more than 50 g / kg. The total recovery of the monomers was 85% by weight (compared to the FDCA produced).

[0177] 2,5-FDCA was recovered in the acid form by a precipitation process with 5M dilute sulfuric acid. The precipitated solid was recovered by candle filtration of the resulting slurry, then washed and dried.

[0178] The composition of the obtained FDCA was analyzed by liquid chromatography to evaluate the purity of the monomer itself as described above.

[0179] The residual sulfate content was evaluated by ion chromatography with a conductivity detector (Metrohm CI-CD) using a "Metrosep A Supp 5" column (250 mm×4.0 mm×5 μm) with polyvinyl alcohol with quaternary ammonium groups as the stationary phase (isocratic elution with 3.2 mM Na2CO3+1 mM NaHCO3 aqueous solution; flow rate: 0.7 mL / min; column temperature: 30°C).

[0180] The sulfate content is less than 200ppm.

[0181] The resulting monomer had a purity of 99.5%, a furoic acid content of less than 0.05%, a furancarboxyaldehyde content of 0.3% and a formylfuroic acid content of 0.02%.

Claims

1. A 2,5-furandicarboxylic acid (FDCA) composition, characterized in that: Compared with the weight of FDCA, the purity of 2,5-furandicarboxylic acid is greater than 99%, the inorganic salt content is less than 500 ppm and the residual monocarboxylic acid content is less than 1% by weight.

2. The FDCA composition according to claim 1, which is obtained by a synthesis method of 2,5-furandicarboxylic acid (FDCA), the method comprising the following steps: 1) oxidizing an aqueous solution of 5-hydroxymethylfurfural (HMF) at a temperature above 100° C. in the presence of molecular oxygen, a heterogeneous catalyst comprising ruthenium and a strong base to obtain a reaction product in aqueous solution comprising a salt of FDCA acid; 2) separating the heterogeneous catalyst from the reaction product in aqueous solution, 3) Reusing the heterogeneous catalyst in the oxidation reaction in step 1).

3. The FDCA composition according to claim 1, wherein the strong base has a solubility of 45 g / l or more in water at 25°C.

4. The FDCA composition according to any one of claims 2 to 3, wherein the pH is maintained at 6.5 to 9 during the oxidation in step 1).

5. The FDCA composition according to any one of claims 2 to 4, wherein the oxidation in step 1) is carried out at a temperature below 160°C.

6. The FDCA composition according to any one of claims 2 to 5, wherein the heterogeneous catalyst comprising ruthenium is selected from supported ruthenium, supported ruthenium oxide, unsupported ruthenium oxide, supported ruthenium hydroxide, unsupported ruthenium hydroxide and mixtures thereof.

7. The FDCA composition according to any one of claims 2 to 6, wherein the separation of the heterogeneous catalyst in step 2) is carried out by at least one operation selected from the group consisting of filtration, decantation, centrifugation and separation by an electrochemical cell, an electrostatic precipitator, a wet scrubber or a hydrocyclone.

8. The FDCA composition according to claim 7, wherein the separation of the heterogeneous catalyst in step 2) is carried out via at least one tangential flow microfiltration.

9. The FDCA composition according to any one of claims 2 to 8, wherein the catalyst is washed and / or regenerated after step 2) and before reuse in step 3).

10. The FDCA composition according to any one of claims 2 to 9, wherein after step 2), the reaction product in aqueous solution is purified by at least one nanofiltration operation.

11. The FDCA composition according to claim 9 or 10, wherein the catalyst is washed with water and the resulting catalyst wash water is used in a purification operation by nanofiltration.

12. The FDCA composition according to any one of claims 2 to 11, wherein the reaction product in aqueous solution is subjected to neutralization, and the FDCA acid obtained in solid form is subsequently isolated.

13. Use of the FDCA composition according to any one of claims 1 to 12 in a polymerization reaction.

14. A method for purifying FDCA, comprising a step of nanofiltration of an aqueous solution of FDCA in dissociated form, followed by a step of precipitating FDCA and a step of washing the obtained solid form of FDCA with water.

Citation Information

Patent Citations

  • Process for the synthesis of 2,5-furandicarboxylic acid.

    EP2601182B1

  • Process for the synthesis of 5-hydroxymethylfurfural from saccharides

    EP2994458B1

  • Process for the production and isolation of 5-hydroxymethylfurfural

    EP3207032B1

  • Hydroxymethyl Furfural Oxidation Methods

    US20080103318A1

  • Process for the oxidation of 5-hydroxymethylfurfural

    US4977283A